OPTIMALISASI KINERJA DAN KEPUASAN KERJA PADA YAYASAN PENDIDIKAN TINGGI NAHDLATUL ULAMA (YAPTINU) JEPARA - Sutarya, Sutarya (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
Nahdlatul Ulama Higher Education Foundation (YAPTINU) Jepara, established by the Head of the Ma'arif Jepara Educational Institution (LP) Branch on March 17, 1989 with the notary deed of Benyamin Kusuma, SH number 5, 1989 which manages three tertiary institutions, namely the first: the Islamic Nahdlatul Ulama Institute (INISNU) Jepara which has a scientific concentration in the religious field which consists of the faculties: Tarbiyah, Sharia, and Dakwa. The second is the Nahdlatul Ulama College of Economics (STIENU) Jepara which has a scientific concentration in the economics field with Study Programs: Accounting (S 1), and Management (S 1). The third is the Nahdlatul Ulama College of Technology and Design (STTDNU) Jepara which has a concentration in technology and design with Study Programs: Industrial Engineering (S 1) and Product Design (S 1). In carrying out the duties and functions of each tertiary institution according to their field, and this is what makes the three of them different, on the other hand it will actually give a color that is an attraction for the people in Jepara and its surroundings. Lecturers as teaching staff at tertiary institutions under the auspices of YAPTINU, have the task of carrying out the tridharma of higher education which includes education and teaching, research and community service. Of the three activities, it shows that the performance of YAPTINU lecturers has not fully met expectations, and also that the problem of job satisfaction of lecturers has not been fully achieved.